Do Individual Risk Attitudes, Experience, and Organizational Culture Influence the Conservatism of Indonesian Auditors? - Maradona, Agus Fredy (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 15 No 1 (2020)DO - 10.24843/JIAB.2020.v15.i01.p01, 2020)
This study examines the effects of individual risk attitudes, professional experiences, and organizational cultures on auditor conservatism in Indonesia. On the basis of a factorial survey involving 153 auditors in three major cities in Indonesia (Jakarta, Surabaya, and Denpasar), this study finds strong evidence that, compared with others, auditors with a lower tendency to take risks and those who have less professional experience tend to be more conservative when performing audit tasks. Nonetheless, this study does not find evidence of the influence of organizational culture on auditor conservatism. Overall, the findings of this study could be of interest to professional associations, regulatory bodies, and other policymakers in Indonesia and other countries as they attempt to constrain aggressive reporting through high-quality independent audits by public accountants in their jurisdictions. Keywords: Auditor conservatism, risk attitude, experience, organisational culture, auditing standards